Physical activity and body composition outcomes of the GreatFun2Run intervention at 20 month follow-up - Nevill Alan; Brown Susie; Musson Hayley; Morris John G; Gorely Trish; Nevill Mary E (BMC, 2011)
Abstract Background Physical inactivity is recognised as a public health concern within children and interventions to increase physical activity are needed. GreatFun2Run was a school-based healthy lifestyles intervention that showed positive changes in physical activity levels and body composition immediately post-intervention. The purpose of this paper was to examine whether these changes in physical activity and body composition were maintained 18-20 months after the intervention ended. Method Participants (n = 589, aged 7-11 yrs) from 4 intervention and 4 control schools took part in the 10-month intervention, of which 421 (71%) were present for follow-up. The intervention comprised a CD-rom learning and teaching resource for teachers; an interactive website for pupils, teachers and parents; two highlight physical activity events (1 mile school runs/walks); a local media campaign; and a summer activity wall planner and record. Randomisation was not possible because of local media content. Outcome measures were objectively measured physical activity (pedometers and accelerometers) and body composition variables (body mass index, waist circumference, estimated percent body fat, and sum of skinfolds). Teacher interviews and participant focus groups were conducted. Multi-level modelling was employed for the data analysis. Results Both control and intervention participants had increased their physical activity at follow-up but there was no group by time interaction (control: 2726 steps per day increase; intervention 3404 steps per day increase, p > .05). There were significant increases in estimated percent body fat, sum of skinfolds, waist circumference and body mass index (BMI) with increasing age. In the control group, there was evidence for a plateauing in the rate of change in all body composition variables with increasing age, except BMI. In contrast, significant interaction terms suggest that the rate of change in waist circumference, BMI and BMISDS continued to increase with age in the intervention group. Teacher interviews suggested that because of time pressures, competing resources, curriculum demands and staff changes the majority of teachers had not continued to use the resources. Conclusions While the intervention initially produced positive changes in physical activity levels and body composition, these changes were not sustained once the intervention ended. Facilitating long-term health behaviour change in children remains a challenge.